Cement adhesive for seawater-erosion-resistant extra-high voltage porcelain insulator and preparation method of cement adhesive
By using cement glue agents prepared by materials such as ferroalaluminate cement, artificial porcelain sand and silicon carbide whiskers, the problem of poor corrosion resistance of ceramic insulators in the prior art is solved, and the resistance to seawater corrosion and service life of porcelain insulators is significantly improved.
Patent Information
- Application Number
- CN202411853699.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-18
AI Technical Summary
The existing cement glue for ultra-high voltage porcelain insulators is poorly corrosive in seawater, resulting in short life and high cost of porcelain insulators, which affects the safety of ultra-high voltage lines.
Ferroaluminate cement and artificial porcelain sand are used to replace traditional silicate cement and river sand, and silicon carbide whiskers and appropriate amounts of anti-cracking agent, water reducing agent and defoaming agent are added to prepare a cement cement for anti-seawater erosion ultra-high pressure porcelain insulators.
It significantly improves the resistance to seawater corrosion and chloride ion corrosion of cement adhesives, improves the mechanical properties and long-term stability of porcelain insulators, and meets the application requirements of marine engineering.
Smart Images

Figure BDA0005191214860000031 
Figure BDA0005191214860000041 
Figure BDA0005191214860000042
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electric power ultra-high voltage, and in particular to a cement adhesive for ultra-high voltage porcelain insulators resistant to seawater erosion and a preparation method thereof. Background Art
[0002] In the UHV transmission and transformation projects of the State Grid, compared with glass insulators and composite insulators, porcelain insulators occupy an extremely important position in the project due to their excellent comprehensive performance such as high temperature resistance and high strength. The reliability of their performance is directly related to the safety and reliability of the UHV line project. The main components of porcelain insulators are porcelain parts, cement adhesives and hardware. They are mainly used to fill the gap between UHV porcelain and metal accessories, between porcelain parts or between glass parts, and make them permanently connected after solidification. Compared with porcelain parts and hardware, cement adhesives have more factors affecting their performance degradation, especially in coastal applications. The erosion of seawater will cause the destruction of cement structures. At present, most UHV manufacturers use silicate cement as a cementing material, and add river sand or quartz sand and water as fillers. The corrosion resistance of silicate cement is poor, and there are more impurities in the river sand and quartz sand used. In the marine environment, the prepared silicate cement adhesive is difficult to meet the requirements of marine engineering. The service life of porcelain insulators is short and the replacement frequency is high. Not only is the cost high, but it also greatly affects the safety of UHV line operation. Therefore, it is urgent to develop a cement adhesive for porcelain insulators that can meet the requirements of high seawater erosion resistance and seawater corrosion resistance. Summary of the invention
[0003] The present invention aims to solve the disadvantages of the existing technology of using silicate cement to prepare cement adhesive, such as poor seawater corrosion resistance, and provides a cement adhesive for seawater-resistant ultra-high voltage porcelain insulators and a preparation method thereof.
[0004] To achieve the above object, the technical solution adopted by the present invention is:
[0005] A cement adhesive for seawater erosion resistant ultra-high voltage porcelain insulators, the cement adhesive comprises the following components in weight percentage: 40-60wt% of ferroaluminate cement, 30-50wt% of artificial porcelain sand, 3-5wt% of cement expansion agent, 0.5-5wt% of silicon micropowder and 0.5-5wt% of silicon carbide whisker, the sum of the above components is 100%, the cement adhesive also comprises an externally added anti-cracking agent, a water reducing agent and a defoaming agent, the external addition amounts of the anti-cracking agent, the water reducing agent and the defoaming agent are 0.1-0.3wt%, 0.1-0.3wt% and 0.1-0.5wt% respectively.
[0006] Preferably, the length of the silicon carbide whisker is 5-10 μm, and the aspect ratio is 5-20.
[0007] Preferably, the main components of the cement expansion agent are: anhydrous calcium sulphoaluminate and calcium aluminate, and the particle size of the cement expansion agent is ≤10 μm.
[0008] Preferably, the preparation method of the artificial porcelain sand is:
[0009] The coal gangue with aluminum content of 35-55% is used as raw material, and after adding water and grinding, iron is removed to control the iron content below 1.5wt%, a certain amount of industrial alumina, washed kaolin, dispersant, etc. are added for ball milling and wet mixing for more than 20 hours, and spray drying is performed to form balls with a particle size of 0.2-0.5mm. A certain amount of plasticizer, such as 0.2-0.3wt% of polyvinyl alcohol or yellow dextrin, is added, and dry pressed into a brick blank, and then dried at 110℃ for more than 20 hours, and placed in a tunnel kiln for sintering, and the highest sintering temperature is 1400℃ for more than 10 hours. After cooling, the brick blank is placed in a crusher for crushing, and then sieved, and the powder of 30-70 mesh is selected as the required artificial porcelain sand.
[0010] Preferably, based on coal gangue, the content of industrial alumina is 5-25%, the content of washed kaolin is 10-30%, and the content of dispersant is 0.4%.
[0011] Preferably, the dispersant is sodium polyacrylate.
[0012] Preferably, the water reducer is a polycarboxylic acid type water reducer.
[0013] Preferably, the defoamer is a silicone defoamer.
[0014] Preferably, the ferroaluminate cement is 525# cement.
[0015] Preferably, the main component of the silicon micropowder is silicon dioxide, with a purity of >99wt% and a fineness of ≤1μm.
[0016] Preferably, the particle size of the artificial porcelain sand is between 30 and 70 meshes.
[0017] Preferably, the artificial porcelain sand comprises alumina, silica and ferric oxide, the content of the alumina is 45wt% to 70wt%, the content of the silica is 30wt% to 55wt%, and the content of the ferric oxide is less than 1.5wt%.
[0018] Preferably, the 28-day seawater erosion resistance coefficient of the cement adhesive is greater than 1.2, and the 28-day chloride ion erosion resistance coefficient is less than 0.2×10 -12 m 2 / s.
[0019] Preferably, the anti-cracking agent is polypropylene fiber with a length of 4-8 mm and an aspect ratio of 5-20.
[0020] The preparation method of the cement adhesive comprises the following steps: premixing ferroaluminate cement, artificial porcelain sand, cement expansion agent, silicon micropowder and silicon carbide whisker to obtain a premix, then adding an anti-cracking agent, a water reducing agent and a defoaming agent to the premix, then adding water and stirring evenly, and performing mold forming and curing to obtain the cement adhesive.
[0021] The UHV referred to in the present invention is divided into UHV AC and UHV DC. UHV AC (UHV) refers to voltages of 1000 kV and above, and UHV DC refers to voltages of ±800 kV and above.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1) Using ferroaluminate cement to replace traditional silicate cement, due to the high content of iron phase in cement, the iron-containing AFt in the cement paste has a higher stability and does not convert into AFm phase, which is an important reason for its excellent resistance to sulfate and chloride ion corrosion, thereby increasing resistance to seawater corrosion;
[0024] 2) Using industrial solid waste coal gangue as raw material, synthesizing artificial porcelain sand with mullite and corundum as main crystal phases to replace existing river sand and quartz sand, greatly improving the seawater erosion resistance, while reducing production costs and realizing the effective utilization of solid waste resources;
[0025] 3) Using silicon carbide whiskers with excellent seawater corrosion resistance as reinforcing materials greatly improves the mechanical properties and long-term stability of cement adhesives, including flexural strength and compressive strength.
[0026] 4) The 3d compressive strength of the prepared cement adhesive is about 100MPa, the flexural strength is above 16MPa, the 28-day seawater erosion resistance coefficient is greater than 1.2, the 6-month compressive strength is greater than 100MPa, and the 28-day chloride ion erosion resistance coefficient is less than 0.2×10 -12 m 2 / s, the adhesive has no obvious deterioration and corrosion phenomenon, and the prepared porcelain insulator has excellent performance and fully meets the application requirements in marine engineering.
[0027] The technical solution of the present invention is simple, the construction operation is convenient, and the maintenance period is short. It can not only greatly improve the product performance and production efficiency, but also provide a porcelain insulator suitable for high requirements for resistance to seawater erosion, thereby greatly improving the safety and service life of the porcelain insulator in resisting seawater erosion. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1This is a SEM picture of the synthetic artificial porcelain sand of the present invention. The microstructure of the prepared synthetic porcelain sand is dense, almost pore-free, and the size is 5 to 20 μm. This structure gives the cement adhesive a higher strength, thereby improving the adhesive's resistance to seawater erosion.
[0029] Figure 2 This is the appearance of silicon carbide whiskers. It shows that the whiskers have a uniform structure and a length of 5 to 10 μm. This structure gives the adhesive higher strength and toughness, while the material itself is also conducive to anti-seawater erosion performance. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] The present invention provides a cement adhesive for anti-seawater erosion ultra-high voltage, which uses ferroaluminate cement, artificial porcelain sand, cement expansion agent, high-purity silicon powder, and high-purity silicon carbide whisker as main raw materials, and adds appropriate amounts of polypropylene fiber, polycarboxylic acid water reducer and defoamer as admixtures. The above materials are mixed evenly according to a certain ratio, and cured in 70°C hot water for 2 hours to obtain the cement adhesive.
[0032] The particle size requirements of different raw materials and their mass fractions are shown in Table 1. The particle sizes and mass fractions of different components fluctuate within the specified range, and the sum of the mass fractions of the main raw materials is required to be 100%.
[0033] Table 1 Particle size and mass fraction of different raw materials
[0034]
[0035]
[0036] Example 1
[0037] This embodiment provides a cement adhesive for anti-seawater erosion ultra-high voltage, with ferroaluminate cement, artificial porcelain sand, cement expansion agent, high-purity silicon powder, high-purity silicon carbide whisker as main raw materials, and appropriate amounts of polypropylene fiber, polycarboxylic acid water reducer and defoamer as admixtures. The above materials are mixed evenly according to a certain ratio, and cured in 70°C hot water for 2 hours to obtain the cement adhesive. The mass content of each component and the performance of the cement adhesive prepared in this embodiment are shown in Table 2.
[0038] Table 2
[0039]
[0040] Example 2
[0041] This embodiment provides a cement adhesive for anti-seawater erosion ultra-high voltage, with ferroaluminate cement, artificial porcelain sand, cement expansion agent, high-purity silicon powder, high-purity silicon carbide whisker as main raw materials, and appropriate amounts of polypropylene fiber, polycarboxylic acid water reducer and defoamer as admixtures. The above materials are mixed evenly according to a certain ratio, and cured in 70°C hot water for 2 hours to obtain the cement adhesive. The mass content of each component and the performance of the cement adhesive prepared in this embodiment are shown in Table 3.
[0042] Table 3
[0043]
[0044]
[0045] Example 3
[0046] This embodiment provides a cement adhesive for anti-seawater erosion ultra-high voltage, with ferroaluminate cement, artificial porcelain sand, cement expansion agent, high-purity silicon powder, high-purity silicon carbide whisker as main raw materials, and appropriate amounts of polypropylene fiber, polycarboxylic acid water reducer and defoamer as admixtures. The above materials are mixed evenly according to a certain ratio, and cured in hot water at 70°C for 2 hours to obtain the cement adhesive. The mass content of each component and the performance of the cement adhesive prepared in this embodiment are shown in Table 4.
[0047] Table 4
[0048]
[0049] Example 4
[0050] This embodiment provides a cement adhesive for anti-seawater erosion ultra-high voltage, with ferroaluminate cement, artificial porcelain sand, cement expansion agent, high-purity silicon powder, high-purity silicon carbide whisker as main raw materials, and appropriate amounts of polypropylene fiber, polycarboxylic acid water reducer and defoamer as admixtures. The above materials are mixed evenly according to a certain ratio, and cured in 70°C hot water for 2 hours to obtain the cement adhesive. The mass content of each component and the performance of the cement adhesive prepared in this embodiment are shown in Table 5.
[0051] Table 5
[0052]
[0053] Comparative Example 1
[0054] This comparative example provides a cement binder for ultra-high voltage anti-seawater erosion, the main components and process of which are the same as those of Example 1, except that 45wt% river sand is used instead of the artificial synthetic porcelain sand in the present invention. The mass content of each component and the performance of the cement binder prepared in Comparative Example 1 are shown in Table 6.
[0055] Table 6
[0056]
[0057]
[0058] The 3d compressive strength of the samples at different seawater erosion ages was 78.2 MPa, while the compressive strength after 12 months decreased to 68.5 MPa. The chloride ion corrosion resistance coefficient after 28 days was 0.8×10 -12 m 2 / s, the 28-day seawater erosion resistance coefficient is 0.88, and there are fine cracks on the surface after 12 months of erosion. Its compressive strength at different ages in seawater is significantly lower than that of Example 1, and its seawater erosion resistance is significantly lower than that of Example 1.
[0059] Comparative Example 2
[0060] This comparative example provides a cement binder for ultra-high voltage anti-seawater erosion, the main components and process of which are the same as those of Example 1, except that 49wt% river sand is used instead of the artificial synthetic porcelain sand in the present invention, and no silicon carbide whisker is added. The mass content of each component and the performance of the cement binder prepared in Comparative Example 1 are shown in Table 7.
[0061] Table 7
[0062]
[0063] The 3d compressive strength of the samples at different seawater erosion ages was 58.4 MPa, while the compressive strength after 12 months decreased to 50.3 MPa. The chloride ion corrosion resistance coefficient after 28 days was 1.15×10 -12 m 2 / s, the 28-day seawater erosion resistance coefficient is 0.82, and there are fine cracks on the surface after 12 months of erosion. Its compressive strength at different ages in seawater is significantly lower than that of Example 1, and its seawater erosion resistance is significantly lower than that of Example 1.
[0064] The above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, so the obvious changes or modifications derived are still within the protection scope of the invention.
Claims
1. A cement adhesive for ultra-high voltage porcelain insulators resistant to seawater erosion, characterized in that: The cement adhesive comprises the following components in weight percentage: 40-60wt% of ferroaluminate cement, 30-50wt% of artificial porcelain sand, 3-5wt% of cement expansion agent, 0.5-5wt% of silicon micropowder and 0.5-5wt% of silicon carbide whisker, the sum of the above components is 100%, and the cement adhesive also includes externally added anti-cracking agent, water reducing agent and defoaming agent, and the external addition amounts of the anti-cracking agent, water reducing agent and defoaming agent are 0.1-0.3wt%, 0.1-0.3wt% and 0.1-0.5wt% respectively.
2. The cement adhesive according to claim 1, characterized in that: The length of the silicon carbide whisker is 5-10 μm, and the aspect ratio is 5-20.
3. The cement adhesive according to claim 1, characterized in that: The main components of the cement expansion agent are anhydrous calcium sulphoaluminate and calcium aluminate, and the particle size of the cement expansion agent is ≤10 μm.
4. The cement adhesive according to claim 1, characterized in that: The ferroaluminate cement is 525# cement.
5. The cement adhesive according to claim 1, characterized in that: The main component of the silicon micropowder is silicon dioxide, the purity is greater than 99wt%, and the fineness is less than or equal to 1μm.
6. The cement adhesive according to claim 1, characterized in that: The particle size of the artificial porcelain sand is between 30 and 70 meshes.
7. The cement adhesive according to claim 1, characterized in that: The artificial porcelain sand comprises aluminum oxide, silicon dioxide and ferric oxide, wherein the content of the aluminum oxide is between 45wt% and 70wt%, the content of the silicon dioxide is between 30wt% and 55wt%, and the content of the ferric oxide is less than 1.5wt%.
8. The cement adhesive according to claim 1, characterized in that: The cement adhesive has a 28-day seawater erosion resistance coefficient greater than 1.2 and a 28-day chloride ion erosion resistance coefficient less than 0.2×10 -12 m 2 / s.
9. The cement adhesive according to claim 1, characterized in that: The anti-cracking agent is polypropylene fiber with a length of 4-8 mm and an aspect ratio of 5-20.
10. A method for preparing the cement adhesive according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: premixing ferroaluminate cement, artificial porcelain sand, cement expansion agent, silicon micropowder and silicon carbide whisker to obtain a premix, then adding an anti-cracking agent, a water reducing agent and a defoaming agent to the premix, then adding water and stirring evenly, and performing mold forming and curing to obtain the cement adhesive.
Citation Information
Patent Citations
Ceramic lever and a process of ceramic lever strengthening
CA2612517A1
Anti-erosion marine concrete and preparation method thereof
CN116375422A
Cement adhesive as well as preparation method and application thereof
CN116425479A
High-performance concrete with high seawater corrosion resistance and preparation method thereof
CN117185754A